Atomic-scale perturbation of oxygen octahedra via surface ion exchange in perovskite nickelates boosts water oxidation - Jumi Bak (Nature Portfolio, 2019)
While perovskite oxides are well-studied for their oxygen electrocatalysis performances, the impact of oxygen octahedra is less studied. Here, authors show electrochemical exchange of lanthanide nickelate surfaces to distort oxygen octahedra, facilitating charge transfer and improving catalysis.